Cytotoxic (9βH)‐Pimarane and (9βH)‐17‐Norpimarane Diterpenes from the Tuber of Icacina trichantha. Issue 12 (December 2014) - Monday Onakpa, Michael; Zhao, Ming; Gödecke, Tanja; Chen, Wei‐Lun; Che, Chun‐Tao; Santarsiero, Bernard D.; Swanson, Steven M.; Uzoma Asuzu, Isaac
Abstract Three (9βH)‐pimaranes, 1, 2, and 3, and two (9βH)‐17‐norpimaranes, 4 and 5, belonging to a rare compound class in nature, were obtained from the tubers of Icacina trichantha for the first time. Compound 1 is a new natural product, and 2–5 have been previously reported. The structures were elucidated based on NMR and MS data, and optical rotation values. The absolute configurations of (9βH)‐pimaranes were unambiguously established based on X‐ray crystallographic analysis. Full NMR signal assignments for the known compounds 2, 4, and 5, which were not available in previous publications, are also reported. All five isolates displayed cytotoxic activities on MDA‐MB‐435 cells (IC50 0.66–6.44 μM), while 2, 3, and 4 also exhibited cytotoxicities on HT‐29 cells (IC50 3.00–4.94 μM).